The Validity of Standard Clauses on Parking Tickets in the Perspective of Consumer Protection - Faisal Hambali; Rois Harliyanto (Journal of Social Science, 2026)
This research is motivated by the continued use of standard clauses in parking tickets stating that the parking operator is not responsible for the loss of vehicles. Such clauses raise legal issues because they potentially transfer the responsibility of business actors to consumers and contradict the principles of consumer protection. This study aims to analyze the regulation of exoneration clauses in parking tickets based on Article 18 of Law Number 8 of 1999 concerning Consumer Protection and to examine the legal consequences of including such clauses. This research employs a normative juridical method using statutory, conceptual, and case approaches. The data were obtained through library research and supported by interview results. The findings indicate that clauses stating that vehicle loss is not the responsibility of the parking operator are contrary to Article 18 paragraph (1) letter a of the Consumer Protection Law because they contain elements of transferring the responsibility of business actors to consumers. Based on the Supreme Court Decision Number 3416 K/Pdt/1995, the legal relationship between parking operators and consumers constitutes a bailment relationship, thereby requiring parking operators to remain responsible for vehicles under their control. Consequently, such clauses are null and void and have no binding legal force upon consumers.